The long outburst of the black hole transient GRS 1716–249 observed in the X-ray and radio band. Issue 2 (9th October 2018) - Bassi, T; Del Santo, M; D'Aì, A; Motta, S E; Malzac, J; Segreto, A; Miller-Jones, J C A; Atri, P; Plotkin, R M; Belloni, T M; Mineo, T; Tzioumis, A K
Abstract: We present the spectral and timing analysis of X-ray observations performed on the Galactic black hole transient GRS 1716–249 during the 2016–2017 outburst. The source was almost continuously observed with the Neil Gehrels Swift Observatory from 2016 December until 2017 October. The X-ray hardness ratio and timing evolution indicate that the source approached the soft state three times during the outburst, even though it never reached the canonical soft spectral state. Thus, GRS 1716–249 increases the number of black hole transients showing outbursts with 'failed' state transition. During the softening events, XRT and BAT broad-band spectral modelling, performed with thermal Comptonization plus a multicolour disc black-body, showed a photon index (Γ < 2) and an inner disc temperature ( kT in = 0.2–0.5 keV) characteristic of the hard intermediate state. This is in agreement with the root mean square amplitude of the flux variability (rms > 10 per cent ). We find that, coherently with a scenario in which the disc moves closer to the compact object, the accretion disc inner radius decreases with the increase of the inner disc temperature, until a certain point when the temperature starts to increase at constant radius. This, in addition with the spectral analysis results, suggests that either the accretion disc reached the innermost stable circular orbit during the hard intermediate state or the hot accretion flow might recondensate in an inner mini-disc. We report on the radio observations performed during the outburst finding that GRS 1716–249 is located on the radio-quiet 'outlier' branch of the radio/X-ray luminosity plane.